Coarse-grained molecular dynamics simulation of cis-1, 4-polyisoprene with silica nanoparticles under extreme uniaxial tension. (1st June 2021) - Yuan, Bin; Zeng, Fanlin; Peng, Chao; Wang, Youshan
Abstract: Coarse-grained (CG) cis-1, 4-polyisoprene (PI) models with multiple silica nanoparticles (NPs) are built to study the effect of NPs and crosslinks in the uniaxial tensile simulation. The potential functions of the CG models are obtained mainly via the iterative Boltzmann inversion method. The tensile simulation results show that the grafted silica NPs and the crosslinked structure play reinforcing roles while the smooth silica NPs do the opposite, which have the similar trends with the experiment results. The differences of mechanical properties for these models are studied from different microscopic aspects, such as the network of NPs, the bond lengths, the free molecular chains, the entanglements, the stress and strain distribution and the microvoid evolution. As a result, the main reasons for the weakening of PI models with smooth silica NPs come from the weak interfacial interaction, the inhomogeneity of structural deformation and the reduction of the number of entanglements. However, if there are graft chains, the interfacial interaction can be enhanced by entangling with the matrix molecular chains. The graft chains can make it possible for the aggregated NPs to separate and can hinder the growth of microvoids at the interface. In addition, the inconsistency of the stress and strain distributions at the microscopic level is verified and the nucleation mechanism of microvoids is believed to be caused by the local violent movement of molecular chains.